Perancangan Interior Holistic Tea House di Malang - Jennifer Chandra (Intra, 2017)
Holistic tea house is a facility which is designed to bring back citizens’s awareness about Indonesia’s local potential which is tea, especially in Malang, East Java. The concept used is “Biophilic”, which is applied to “Secret Garden” theme. Both concept and theme were chosen to create the nuance of garden in attractive and soothing ways which are already difficult to find in big cities nowaday so that citizens are interested in learning more about tea. The concept also can be seen from the use of nature materials and colors, the application of different atmosphere from every rooms but still give the spacious feeling and creating space in space.